Knowledge and behavior of primary health care dentists in the Municipality of Cascavel - PR regarding suspicious lesions and malignant oral neoplasms (Research, Society and Development, 2022)
Objective: To analyze the knowledge and behavior of dentists (CD's) working in Primary Health Care (PHC) in the Municipality of Cascavel - PR, regarding the early detection and management of suspicious lesions and malignant oral neoplasms. Methods: This is a cross-sectional, descriptive study with a quantitative approach. Data collection was carried out through a structured questionnaire delivered to the CD's working in the PHC in the municipality of Cascavel - PR between the months of July and November 2021. Results: 30 professionals adhered to the survey, of which 80% evaluated their knowledge as regular. Only 23.3% use this knowledge to perform a detailed clinical examination with attention to detecting oral lesions in all patients. In addition, although most (90.7%) indicated positively about feeling safe in guiding patients on prevention and self-examination, only 16.7% indicated that they always carry out these guidelines. Conclusion: Most of the professionals interviewed have satisfactory knowledge about oral cancer, at the same time they demonstrate fragility regarding behavior regarding actions aimed at education and early detection of oral cancer. Evidencing the need for actions so that the weaknesses and insecurities of these professionals are overcome.